A voice of her own women and economic change in Asia - Carroll, Ann.; Kalin, Andrea; Westfall, Matthew; Asian Development Bank. Information Office (Mandaluyong, Metro Manila ADB, 1997)
Profiles the challenges and changes faced by women. In Cambodia, rural poor women are learning to read for the first time. In the Philippines, enterprising women are creating homegrown opportunities for employment. And in Bangladesh, the ready made garment industry has recast the traditional image of women.
Editor, Michelle Green; Narrator, Melissa Leebaert.
Keywords: Women -- Social conditions. -- Cambodia; Women -- Social conditions. -- Bangladesh; Women -- Social conditions. -- Philippines